Analysis on the convergence practice of district level convergence media centre in Yuncheng city - Xinhu, Xu; Mahamed, Mastura; Sha'rl, Sharil Nizam (Human Resource Management Academic Research Society, 2023)
In China, the construction of district and county-level convergence media centres is currently experiencing an upward stage. The construction of district and county-level convergence media centres began nationwide in 2018, and their primary responsibility is to assist the government to complete its functional transformation as well as to cooperate with the implementation of rural revitalisation plans. According to previous literature, the construction and operation of district and county-level convergence media centres are not perfect, and many common problems have emerged, which are difficult to solve. This study was a mixed study, a total of 79 valid questionnaires were received by sending electronic versions through WeChat. In general, the construction of convergence media centres at the district and county levels is still imperfect at this stage, there are no effective top-level designs, funds, talents or policies, and it is difficult to effectively support convergence media as the internal structure of the centre is fused.